Genetic Evolution Characteristics of Genotype G57 Virus, A Dominant Genotype of H9N2 Avian Influenza Virus - Wang, Jinfeng; Jin, Xuanjiang; Hu, Jingkai; Wu, Yifan; Zhang, Mengmeng; Li, Xiao; Chen, Jianglin; Xie, Shumin; Liu, Jing; Qi, Wenbao; Liao, Ming; Jia, Weixin (Frontiers in Microbiology, 2021)
This study is an investigation of the evolution of the H9N2 avian influenza virus. Whole genome phylogenetic trees were constructed based on 306 H9N2 avian influenza isolates collected in China from 2014 to 2019.Results showed that 8 gene fragments clustered separately by their dominant clades and that 10 genotypes were identified, 7 of which were novel types. The G57 genotype was confirmed as the most common with a frequency of 94%. In China, the G57 genotype of H9N2 first appeared in 2007, then became the most common genotype in 2013. Therefore, the nucleotide replacement rates of G57 genotype in HA and NA genes collected from 2007 to 2019 were estimated.The positive selection pressure sites in the same data set were also counted.Taking 2013 as the boundary, the time period was divided into two periods, 2007-2012 and 2013-2019. From 2007 to 2012, multiple genotypes coexisted and bear the pressure from nature and environment, while G57 genotype was just in the adaptation stage, subject to less selection pressure and in the process of slow evolution. However, from 2013 to 2019, G57 became the dominant genotype, and most of the external pressure acted on G57. G57 genotype, therefore, showed better adaptability than other genotypes. From 2013 to 2019, the results indicated that the nucleotide substitution rate of the HA and NA genes was increasing. In addition, the positive selection pressure on HA and NA genes got stronger comparing to that from 2007 to 2012.To sum up, the absolutely dominant genotype G57, maintained a relatively constant genotype frequency andexperienced intense evolution and adaptive selection at the same time during our monitoring period. Therefore, urgent attention and diligent surveillance of H9N2 avian influenza virus are becoming more and more important.